The Sociology of Artistic Expression and Its Role in the Drawings of Art Education Department Students (Al-Academy, 2025)
The sociology of artistic expression is not a simple process, especially when it represents the ideas of a student who is under the influence of aesthetic emotion and does not merely copy or transmit artwork. Rather, it is a collection of repositories linked to sociological ideas, customs, and traditions, whether this copying is related to nature or from the student's own repertoire of expression and ideas.The sociology of expression explains the artistic preoccupations of art students from a philosophical and artistic perspective, and how to find ways to employ them, what their artistic vision is, and the ways to use these methods in artistic expression and address them among students.The research includes four chapters. The first chapter addresses the research problem, which is summarized in the following questions: (Can artistic expression be used as a sociological function? What are the philosophical and artistic preoccupations of the sociology of artistic expression of art education department students in their productions?) In addition to the importance and objective of the research (monitoring the mechanisms of the sociology of artistic expression), its limits, and defining the terms used in the research topic. The second chapter includes two topics: (The concept of sociology) and its impact on the self and society in general, and (Sociology in artistic expression) and its impact on individuals, literature, and the visual arts (drawing). The third chapter addresses the research sample, research methodology, research tool, and sample analysis. The fourth chapter addresses the most important results, conclusions, and proposed recommendations, as well as a list of sources and references and a summary of the research in both Arabic and English.